Improving Verbal Linguistic Intelligence through The Picture Story Reading Method - Karim, Abdul; Istifadah, Istifadah; Sholehani, Alfianti (Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2023)
Good linguistic verbal intelligence can help children develop speaking skills in front of others. And that will undoubtedly make interacting with the people around him easy. One way to create it is by using storytelling with pictures for children. This research is a case study conducted in a kindergarten in East Java, Indonesia. Researchers collect information using observation, interviews, and documentation. This study analyzes data by reducing, presenting, and concluding. Source and method triangulation is used to verify the correctness of the data. The results of this study are: (1) Planning for learning verbal-linguistic intelligence for children through the picture story method has been carried out through the preparation of semester, weekly, and even daily learning tools. (2) Implementation of verbal-linguistic intelligence learning with the picture story method can produce experiences more binding on children's active participation in class. This method is also proven to help students develop verbal-linguistic skills through understanding stories and mastering new vocabulary. c) evaluation of learning with the picture story method through making checklists, Likert scale questionnaires, and retelling activities. These techniques can simultaneously function as an assessment or diagnostic tool for verbal-linguistic abilities in children. Abstrak Kecerdasan verbal linguistik yang baik dapat membantu anak mengembangkan keterampilan berbicara di depan orang lain. Dan hal itu tentunya akan memudahkan untuk berinteraksi dengan orang-orang disekitarnya. Salah satu cara untuk mengembangkannya adalah dengan menggunakan metode bercerita bergambar untuk anak. Penelitian ini merupakan studi kasus yang dilakukan di sebuah taman kanak-kanak di Jawa Timur, Indonesia. Peneliti mengumpulkan informasi dengan menggunakan observasi, wawancara, dan dokumentasi. Penelitian ini menganalisis data dengan cara mereduksi, menyajikan, dan menyimpulkan. Triangulasi sumber dan triangulasi metode digunakan untuk memverifikasi kebenaran data. Hasil penelitian ini adalah: (1) Perencanaan pembelajaran kecerdasan linguistik verbal untuk anak melalui metode cerita bergambar telah dilaksanakan melalui penyusunan perangkat pembelajaran semester, mingguan, bahkan harian. (2) Penerapan pembelajaran kecerdasan linguistik verbal dengan metode cerita bergambar dapat menghasilkan pengalaman yang lebih mengikat partisipasi aktif anak di kelas. Metode ini juga terbukti membantu siswa mengembangkan keterampilan linguistik verbal melalui pemahaman cerita dan penguasaan kosa kata baru. c) evaluasi pembelajaran dengan metode cerita bergambar melalui pembuatan daftar periksa, angket skala Likert, dan kegiatan menceritakan kembali. Teknik-teknik tersebut sekaligus dapat berfungsi sebagai asesmen atau alat diagnostik kemampuan linguistik verbal pada anak